Fabrication and Optical Property of Periodic Sn1-xTixO2 Nanostructures Patterned by the Polystyrene Microsphere Templates. (13th December 2011) - Chen, Shutian; Li, Zhengcao; Zhang, Zhengjun
Abstract : Regular arrays ofSn 1 - x Ti x O 2 nanostructures were fabricated by glancing angle sputter deposition onto self-assembled close-packed arrays of 200 nm diameter, 500 nm diameter, and 1  μ m diameter polystyrene microspheres, respectively. The morphology of the nanostructures could be modulated by the variation of the sputtering power of Ti target and the size of polystyrene microspheres templates. Accordingly, the performance of reflection which was dependent on the morphology of nanostructures could be tuned by optimizing the parameters. The anisotropic morphology of nanoflakes achieved by adjusting the sputtering power of Ti target could generate the anisotropism of reflectance. With the increase of the PS sphere size, the anisotropism of nanostructures weakened; however, they exhibited excellent antireflection effects by creating a smaller gradient of refractive index.